Rancang bangun alat ukur jumlah tetes dan volume sisa cairan infus dengan warning system pada sistem monitoring cairan infus berbasis arduino (Measuring device for the number of drops fabrication design and the volume of remaining infusion fluids with a warning system in the Arduino-based infusion fluid monitoring system) - Auliya Sifa Fauziyyah; - Yohandri (PILLAR OF PHYSICS, 2019)
Intravenous Fluids Drops are very important for the process of healing or treatment for patients. The function of infusion is to replace the loss of fluids or nutrients in the body. In Indonesia, monitoring system of condition about infusion is still done manually, but for the cases such a large hospitals which is the number of patients is not balanced by medical personnel, it is becomes ineffective so that it can cause mistakes in monitoring. A very serious mistake can occur are too late in replacing the infusion. The solution to solve this problem is to make an automatic infusion monitoring system with an alarm warning. This research is eksperimental research. The measurement technique taken is direct and indirect measurement. Direct measurement data is mass of infusion and indirect measurment data is the number of infusion drops and the percentage of infusion volume. The purpose of this research is to determine the design spesifications and peformance spesification of the instrument. The sensor used to measure infusion drops per minute is photogate and to measure the infusion volume is load cell. Motor Servo Tower Pro SG90 are used as automatic drip control and arduino mega used as a brain for this instrument. The display is use TFT LCD and using buzzer for alarm warning. The accuracy of infusion drops per minute system is 0,97 with error 1,25% and accuracy of infusion volume is 0,978 with error 1,944%.